Construction and Regulatory Framework of Wing-In-Ground Effect (WIG) Craft from the Perspective of Safety and High-Speed Craft Classification - Antoni Arif Priadi; Tri Cahyadi; Sahattua P. Simatupang; Winarno Winarno; Larsen Barasa; Natanael Suranta; Mahsa Gyda Rahma; Muhammad Eddy Taufik; Michael Sugiarto Simamora (Dinasti International Journal of Education Management and Social Science, 2026)
Wing-In-Ground (WIG) effect craft represent a compelling high-speed maritime transportation solution for archipelagic nations, yet their global adoption remains constrained by fragmented regulatory frameworks and the absence of nationally adapted construction standards. This study proposes a national regulatory and construction framework for WIG craft tailored to Indonesia's tropical archipelagic conditions, using a systematic mapping study of 32 peer-reviewed and regulatory sources retrieved from Scopus, Web of Science, IEEE Xplore, and ScienceDirect following PRISMA 2020 guidelines. The results establish three key contributions. First, a three-tier classification system (Type A: exclusive ground effect; Type B: transitional capability; Type C: full aircraft mode) is proposed to facilitate phased adoption with progressively stringent certification requirements. Second, a hybrid material strategy combining marine-grade aluminum alloys (hull) with Carbon Fiber Reinforced Polymer (wings and stabilizers) is validated as optimal for tropical corrosion resistance and weight efficiency, with potential payload improvements of 30–40% over all-aluminum designs. Third, a redundant propulsion architecture with multi-stage Foreign Object Damage (FOD) filtration achieving ≥95% particulate removal efficiency is established as mandatory for safe operations in Indonesia's littoral environment. Operational analysis of the Java Sea demonstrates that Type A WIG craft could achieve approximately 80% annual uptime, reducing the Surabaya–Bawean transit from 3–4 hours to 45–60 minutes. This framework addresses the legal vacuum created by the absence of national WIG regulations and provides a replicable model for other tropical archipelagic nations.